SONGEL, F. (2021). El arte de leer las calles. Valencia: Barlin Libros - Torres Morán, Eduardo (Daimon Revista Internacional de Filosofia, 2023)
Reseña del libro: SONGEL, F. (2021). El arte de leer las calles. Valencia: Barlin Libros.